Analysis of Shooting Techniques and Strategies in Football Games at Sumberkare 3 State Elementary School - Purnomo, Purnomo; Sudarsono, Sudarsono (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine the shooting ability in soccer games of students of SDN Sumberkare 3. The subjects of this study were 40 8th grade students of SDN Sumberkare 3. This study is a quantitative descriptive study, the research method is a survey method with data collection techniques using tests and measurements. The data obtained are in the form of test results and measurements of shooting ability in soccer games of SDN Sumberkare 3 students. It can be concluded that the shooting ability in soccer games of SDN Sumberkare 3 students is in the sufficient category for 30 students or 75%, the less category for 6 students or 15%, and the very less category for 4 students or 10%.